Abusive supervision and employee creativity in China: Departmental identification as mediator and face as moderator. Issue 8 (7th November 2016) - Gu, Jibao; Song, Jun; Wu, Jianlin
Abstract : Purpose: The purpose of this paper is to examine how abusive supervision affects employee creativity, incorporating departmental identification as a mediator and face as a moderator based on social identity theory. Design/methodology/approach: The study sample consisted of 207 full-time employees in China. Findings: Results indicate that abusive supervision is negatively related to employee creativity and this relationship is fully mediated by departmental identification. In addition, face held by employees plays a moderating role: the direct effect of abusive supervision on departmental identification and the mediating effect of departmental identification are stronger when face is low rather than high. Practical implications: This study also has major practical implications for organizations. First, the organizations should fully understand the harmfulness of abusive supervision and try to avoid abusive behaviors. Second, the organizations could enhance employee creativity by promoting departmental identification. Third, employees who hold low face should get more attention and support. Originality/value: This study makes several theoretical implications. First, findings contribute to enriching one's understanding of the relationship between abusive supervision and employee creativity in China. Second, the domain of abusive supervision is expanded by empirically testing departmental identification as a crucial psychological mechanism explaining the abusive supervision – employee creativity relationship. Third, this study also advances one's understanding of social identity process by examining empirically moderating effects of cultural value in the relationship between abusive supervision and employee creativity.